The Complete Chloroplast Genome of an Epiphytic Leafless Orchid, Taeniophyllum complanatum: Comparative Analysis and Phylogenetic Relationships - Zhuang Zhou; Jinliao Chen; Fei Wang; Xiaopei Wu; Zhongjian Liu; Donghui Peng; Siren Lan (Horticulturae, 2024)
Taeniophyllum is a distinct taxon of epiphytic leafless plants in the subtribe Aeridinae of Orchidaceae. The differences in chloroplast genomes between extremely degraded epiphytic leafless orchids and other leafy orchids, as well as their origins and evolution, raise intriguing questions. Therefore, we report the chloroplast genome sequence of Taeniophyllum complanatum, including an extensive comparative analysis with other types of leafless orchids. The chloroplast genome of T. complanatum exhibited a typical quadripartite structure, and its overall structure and gene content were relatively conserved. The entire chloroplast genome was 141,174 bp in length, making it the smallest known chloroplast genome of leafless epiphytic orchids. It encoded a total of 120 genes, including repetitive genes, comprising 74 protein-coding genes, 38 transfer RNA (tRNA) genes, and 8 ribosomal RNA (rRNA) genes. A phylogenetic analysis was conducted on the chloroplast genomes of 43 species belonging to five subfamilies of Orchidaceae. The results showed that the five subfamilies were monophyly, with nearly all segments having a 100% bootstrap value. T. complanatum and Chiloschista were clustered together as a sister group to Phalaenopsis and occupied the highest position in the Epidendroideae. Phylogenetic analysis suggested that T. complanatum and other leafless orchids within the Orchidaceae evolved independently. This study may provide the foundation for research on phylogenetic and structural diversity in leafless epiphytic orchids, thereby enhancing the resources available for chloroplast genome studies in Orchidaceae.